A complex analysis of stress intensity factors for two asymmetric and unequal collinear cracks in rocks subjected to compressive and shear loads. (April 2022) - Wang, Hanbing; Huang, Jianwei; Zhu, Zheming; Zhou, Lei; Liu, Ruifeng; Jiang, Yuanfeng
Highlights: The theoretical formulas of the SIFs at crack tips under compressive stress, shear stress and internal pressure were proposed using the complex function method. The theoretical results of the SIFs were compared with numerical results using the ABAQUS code. The effects of outer shear stress, internal pressure, crack distance, crack surface friction and crack length on the SIFs were discussed. Abstract: Crack in the rocks is an important factor of landslide disasters, and cracks may be interconnected to form a large gap under compressive and shear loads. Therefore, it is necessary to study the stability of cracks. In order to study the interaction between multiple cracks, a plane containing two asymmetric and unequal collinear cracks under compressive loads, shear loads and internal pressure was investigated. Complex functions were applied to derive the stress intensity factors (SIFs) of crack tips. The numerical simulation by using the ABAQUS code was conducted to validate the correctness of theoretical solutions, and the numerical results were in good agreement with the theoretical solutions. Then, the effects of outer shear stress, internal pressure, crack distance, crack surface friction and crack length on stress intensity factors of mode II were discussed. We thus can conclude that internal pressure will reduce the friction effect on the crack surface and cause the crack to initiate more easily; the maximum value of K II increases with the outer shear stress increase; the SIFs of internal crack tips are more easily affected by the distance of cracks than that of the external crack tips.